Conceptualization and development of frameworks in literature review: methodological analysis and its implications in scientific research - Aulia, Muhammad; Ardhi, Aisha Satira; Fitriani, Wahidah; Alimin, Miftahul (Institute of Computer Science (IOCS), 2025)
The use of frameworks in research is important, because with it the research to be carried out gets the right direction and a clear position. However, many studies do not use the framework in their implementation or use it but not in depth. This article aims to analyze the role, relevance, and development of frameworks in the cross-disciplinary scientific literature. The framework is understood as a conceptual foundation that connects theories, methodologies, and findings so as to maintain research coherence. This study uses a literature study design by examining articles from accredited national and international journals. Data were collected through the search of various academic databases and analyzed using a thematic approach to identify patterns of conceptualization, relevance, and forms of adaptation of frameworks in various disciplines. The results of the study show that the framework functions strategically in strengthening theoretical foundations, sharpening the identification of research gaps, and guiding the design of contextual and innovative research models. This study confirms that the development of a framework that is adaptive to social, cultural, and disciplinary contexts is key to maintaining relevance and increasing scientific contribution in the midst of the dynamics of knowledge development.